Phylogenetic analysis of promoter regions of human Dolichol kinase (DOLK) and orthologous genes using bioinformatics tools - Farooqi Nadia; Rahman Ataur; Ali Yasir; Ali Kishwar; Khan Muhammad Ezaz Hasan; Jones David Aaron; Abdelkarim Mouadh; Ullah Farman; Jalil Fazal (Open Life Sciences, 2023)
The Dolichol kinase (DOLK) gene encodes the polytopic DOLK protein associated with the endoplasmic reticulum (ER) N-glycosylation pathway catalyzing the final step in the biosynthesis of dolichol phosphate. Dolichol phosphate is an oligosaccharide carrier required for N-glycosylation of DOLK protein, with its deficiency leading to a severe hypo glycosylation phenotype in humans which can cause congenital disorders of glycosylation and death in early infancy. The aim of the present study is to identify the phylogenetic relationship between human and ortholog species based on their conserved sequences in DOLK gene. Sequence alignment of DOLK was carried out in this study and the evolutionarily conserved regulatory sequences were identified using bioinformatics. Promoter sequence of human DOLK was compared with orthologous sequences from different organisms. Conserved non-coding sequences (CNS) and motifs in promoter regions were found by analyzing upstream promoter sequences of Homo sapiens DOLK and its orthologous genes in other organisms. Conserved sequences were predicted in the promoter regions in CNS1 and CNS2. Conserved protein sequences were also identified by alignment of the orthologous sequences. Organisms with similar gene sequences are assumed to be closely related and the ER N-glycosylation pathway is conserved in them.